1997
DOI: 10.1029/97jd01113
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the dry deposition of peroxides to a Canadian boreal forest

Abstract: Abstract. The dry deposition rates of hydrogen peroxide (H202) and total organic peroxides (ROOH) were measured above a coniferous forest in Saskatchewan, Canada. Deposition velocities Vd were obtained from gradient measurements using the modified Bowen ratio method. A diurnal pattern was observed, with highest deposition velocities occurring during the day. Daytime deposition velocities were approximately 5 cm s -• for H20 2 and 1.6 cm s -• for ROOH. Nighttime deposition velocities were much smaller, approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 27 publications
4
33
0
Order By: Relevance
“…The present study suggests a best estimate for the 24 h mean of the dry deposition velocity of hydrogen peroxide of Gao et al (1993) 2.5 above forest Heikes et al (1996) 0.88 1.4×10 −5 South Atlantic Hall and Claiborn (1997) 1-5 coniferous forest in Canada Sillman et al (1998) ≈5 Tennessee Walcek (1987) theoretically calculated a value of 1 cm/s for the H 2 O 2 dry deposition velocity over the northeast United States which is roughly in agreement with our result for the rainforest and with the mean 1-D SCM result over land. Baer and Nester (1992) assessed an average v d (H 2 O 2 )=1.5 cm/s for the region of the Upper Rhine Valley (Germany) in March 1985 with a regional mesoscale diffusion model, again relatively close to our estimate.…”
Section: Comparison With Results From Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study suggests a best estimate for the 24 h mean of the dry deposition velocity of hydrogen peroxide of Gao et al (1993) 2.5 above forest Heikes et al (1996) 0.88 1.4×10 −5 South Atlantic Hall and Claiborn (1997) 1-5 coniferous forest in Canada Sillman et al (1998) ≈5 Tennessee Walcek (1987) theoretically calculated a value of 1 cm/s for the H 2 O 2 dry deposition velocity over the northeast United States which is roughly in agreement with our result for the rainforest and with the mean 1-D SCM result over land. Baer and Nester (1992) assessed an average v d (H 2 O 2 )=1.5 cm/s for the region of the Upper Rhine Valley (Germany) in March 1985 with a regional mesoscale diffusion model, again relatively close to our estimate.…”
Section: Comparison With Results From Other Studiesmentioning
confidence: 99%
“…Also the derived deposition rate of 1.4×10 −5 s −1 for H 2 O 2 (6×10 −6 s −1 for CH 3 OOH) at a marine BL height of 700 m is rather smaller than our value. From gradient measurements (modified Bowen method) Hall and Claiborn (1997) compute diurnal maxima of v d =5 cm/s for H 2 O 2 and 1.6 cm/s for organic peroxide as well as nocturnal values of 1 cm/s and 0.5 cm/s, respectively, over a coniferous forest in Canada. Their results show that the surface resistance is negligible in the case of H 2 O 2 and that the dry deposition of all peroxides is limited by turbulence.…”
Section: Comparison With Results From Other Studiesmentioning
confidence: 99%
“…However, the solubility of many hydroperoxides and other oxygenated organics is extremely uncertain and known to cover a wide range, with the measured Henry's law constants for methyl hydroperoxide and peroxyacetic acid being 2-3 orders of magnitude lower than that for H 2 O 2 (Lind and Kok, 1986). Observations of OVOC deposition velocities are sparse, with only a handful reported for forested regions (Hall and Claiborn, 1997;Valverde-Canossa et al, 29 Figure 13: Diurnal variation of the observed OH reactivity (black points) and a set of model simulations with different first order loss rates to represent the loss of model generated species to physical processes. The lifetime of species with respect to this first order loss are 1 (green), 12 (dark blue), 24 (red) 48 (pale blue), and 96 (yellow) h.…”
Section: Physical Lossmentioning
confidence: 99%
“…However, the solubility of many hydroperoxides and other oxygenated organics is extremely uncertain and known to cover a wide range, with the measured Henry's law constants for methyl hydroperoxide and peroxyacetic acid being 2-3 orders of magnitude lower than that for H2O2 [Lind and Kok, 1986]. Observations of OVOC deposition velocities are sparse, with only a handful reported for forested regions [Hall and Claiborn, 1997;Valverde-Canossa et al, 2006;Hall et al, 1999;Karl et al, 2004;Kuhn et al, 2002]. An observation of the deposition velocity of the sum of MVK and MACR in a Fig.…”
Section: Physical Lossmentioning
confidence: 99%
“…Due to strong mixing within the PBL, air masses near the surface are strongly affected by H 2 O 2 dry deposition. In addition, H 2 O 2 is removed by rainout in the lower troposphere (Heikes et al, 1996b;Hall and Claiborn, 1997;Hall et al, 1999). The combination of these effects results in an inverted "C-shaped" vertical profile for H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%